Treatment of muscle-invasive urothelial cancer with nivolumab (CheckMate 274 study): a plain language summary - Bajorin, Dean F; Witjes, J Alfred; Gschwend, Jürgen E; Schenker, Michael; Valderrama, Begoña P; Tomita, Yoshihiko; Bamias, Aristotelis; Lebret, Thierry; Shariat, Shahrokh F; Park, Se Hoon; Ye, Dingwei; Agerbaek, Mads; et al. (Future oncology (London, England), 2023)
WHAT IS THIS SUMMARY ABOUT?: This is a summary of a paper published in a medical journal that describes the results of a study called CheckMate 274. This study looked at a new treatment for muscle-invasive urothelial cancer, a type of cancer found in the urinary tract that has spread from the inner lining of the urinary tract or bladder and into the surrounding muscle wall where it can then spread to other parts of the body. The standard treatment for muscle-invasive urothelial cancer is surgery to remove affected parts of the urinary tract. However, cancer returns in more than half of people after this surgery. Adjuvant therapy is given to people after surgery with muscle-invasive urothelial cancer with a goal to reduce the risk of the cancer coming back; however, at the time this study started, there was no standard adjuvant treatment. WHAT HAPPENED IN THE STUDY?: In the CheckMate 274 study, researchers compared nivolumab with a placebo as an adjuvant treatment for people with muscle-invasive urothelial cancer. The aim of the study was to understand how well nivolumab worked to reduce the chance of the cancer returning after surgery. The study also looked at what side effects (unwanted or unexpected results or conditions that are possibly related to the use of a medication) people had with treatment. WHAT DO THE RESULTS MEAN?: The results showed that people who received nivolumab versus placebo: Survived longer before the cancer was detected again, including people who had programmed death ligand-1 (shortened to PD-L1) on their cancer cells. Survived longer before a secondary cancer outside of the urinary tract was detected. Experienced no differences in health-related quality of life (the impact of the treatment on a person's mental and physical health). Had similar side effects to the people who received nivolumab in other studies. Clinical Trial Registration: NCT02632409 (ClinicalTrials.gov).
Keywords: plain language summary; immunotherapy; nádory svalů; lay summary; nádory močového měchýře; clinical trial; Muscle Neoplasms; Muscles; kvalita života; Nivolumab; imunoterapie; Humans; urothelial cancer; svaly; Immunotherapy; Urinary Bladder Neoplasms; adjuvant; Quality of Life; bladder cancer; lidé; nivolumab